2017
DOI: 10.5200/sm-hs.2016.118
|View full text |Cite
|
Sign up to set email alerts
|

Slaugytojų žinios ir įgūdžiai atliekant sekreto išsiurbimą iš tracheostomos vamzdelio

Abstract: Raktažodžiai: slaugytojų žinios ir įgūdžiai, sekreto išsiurbimas iš tracheostomos vamzdelio, tracheostomos priežiūra. SantraukaSiekiant sumažinti skyriuose slaugomiems pacientams, kuriems išvesta tracheostoma, priežiūros sukeltų komplikacijų skaičių, labai svarbu, kad slaugytojai sekreto išsiurbimo iš tracheostomos vamzdelio procedūrą atliktų saugiai ir veiktų vadovaudamiesi moksliniais tyrimais pagrįstomis rekomendacijomis. Šio tyrimo tikslas buvo išanalizuoti slaugytojų žinias ir įgūdžius atliekant sekreto i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…This factor may increase the number of complications. In Lithuanian study (2013) most of the nurses (94.9%) from ordinary adult and children departments in the survey stated that they use sterile isotonic solution to tracheostomy tube for suctioning, but observation showed that it was done in significantly less cases (9.3 % comparing with the survey χ²=138,857;lls=1;p<0,001) [22]. In our study, no nurses were observed to actually use normal saline in practice.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This factor may increase the number of complications. In Lithuanian study (2013) most of the nurses (94.9%) from ordinary adult and children departments in the survey stated that they use sterile isotonic solution to tracheostomy tube for suctioning, but observation showed that it was done in significantly less cases (9.3 % comparing with the survey χ²=138,857;lls=1;p<0,001) [22]. In our study, no nurses were observed to actually use normal saline in practice.…”
Section: Discussioncontrasting
confidence: 55%
“…The results of the survey conducted 2013 in Lithuania showed, that more than half of the nurses (60.1%) would do the suctioning from tracheostomy tube at the pressure that is set in the suction machine and more than a tenth (11.9 %) -at the maximum pressure available in suction machine. Observations in departments were tracheostomized patients are moved from intensive care showed that in majority of the cases (86.9%) pressure greater than 150mmHg was used [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation